Comparison of Electrocoagulation Using Iron and Aluminium Electrodes with Chemical Coagulation for removal of Vat Dye Solution - Ainchu, Surangkhana; Yimrattanabovorn, Jareeya; Panomasak, Onin; Toduang, Thanatporn; Klingthale, Sakawduan; Wichitsathian, Boonchai (Naresuan University Journal: Science and Technology (NUJST); Vol 28 No 2 (2020): April-June 2020DO - 10.14456/nujst.2020.11, 2020)
The dyes are widely used in textile industry and causes various environmental problems. There are several methods available for removal of dyes from wastewater but they have been found to exhibit certain limitations. Among these methods, chemical coagulation (CC) and electrocoagulation process (EC) has been successfully used for the treatment of textile wastewater being attractive alternative. The objective of study is to investigate the performance of EC and CC for decolorization of vat dye and to compare between iron and aluminium as electrode and coagulant. The results show EC process had color removal efficiency higher than 90 % for both of Fe and Al electrode. The respective effects of operational parameters (initial dye concentration, reaction time, initial pH and applied voltage) had effect on color removal of EC.  And the optimum conditions for Fe and Al electrode are 28 mg/L for initial dye concentration, 30 and 20 min for reaction time, 5 and 7 for initial pH and 30 volt for applied voltage respectively. A comparison with CC using the same amount of Fe and Al as in EC was also carried out. The EC process show more efficient process than CC process to treat vat dye solution. And for color removal of EC did not differ significantly between Al and Fe electrode.The application of EC to treat wastewater from textile household industries had color and COD removal efficiency higher than 80% and 60% respectively. It was concluded that the EC process is a competitive alternative process and presents a high potentiality for the treatment of color from textile wastewater. Keywords: Electrocoagulation; Chemical Coagulation; Vat Dye; Iron Electrode; Aluminium Electrode